A novel approach to assess radial distribution system for optimal sizing of microgrid - Shalaka Chaphekar; Anjali A. Dharme (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The performance of Radial Distribution System (RDS) is enhanced by maintaining the appropriate Penetration Ratio (PR) of Distributed generation.  However, it has been observed that Penetration Ratio cannot be useful to analyze the impact of a Microgrid on performance of RDS. Hence a new index ‘Relief Factor’ (RF) is defined in this paper and the impact of Microgrid at different RF is studied. This paper presents an approach to compute daily energy losses variation when Microgrids of varying RF are connected to RDS having different maximum demands.  A methodology has been proposed for finding optimal RF and location of Microgrid.  In addition, the impact of maximum demand of RDS on optimum RF is analyzed. This paper gives the novel concept of assessing the RDS for integration of Microgrid based on maximum demand of RDS as well as Microgrid and sizing of Microgrid based on optimum Relief Factor.